Constraining the physical structure of the inner few 100 AU scales of deeply embedded low-mass protostars - Persson, Magnus Vilhelm; Harsono, Daniel; Tobin, J. J.; Dishoeck, E. F. van; Jørgensen, J. K.; Murillo, N.; Lai, S.-P. (Astronomy and astrophysics, 2016)
Context: The physical structure of deeply embedded low-mass protostars (Class 0) on scales of less than 300 AU is still poorlyconstrained. While molecular line observations demonstrate the presence of disks with Keplerian rotation toward a handful of sources,others show no hint of rotation. Determining the structure on small scales (a few 100 AU) is crucial for understanding the physicaland chemical evolution from cores to disks. Aims: We determine the presence and characteristics of compact, disk-like structures in deeply embedded low-mass protostars. Arelated goal is investigating how the derived structure affects the determination of gas-phase molecular abundances on hot-core scales.Methods.Two models of the emission, a Gaussian disk intensity distribution and a parametrized power-law disk model, are fittedto subarcsecond resolution interferometric continuum observations of five Class 0 sources, including one source with a confirmedKeplerian disk. Prior to fitting the models to the de-projected real visibilities, the estimated envelope from an independent model andany companion sources are subtracted. For reference, a spherically symmetric single power-law envelope is fitted to the larger scaleemission (∼1000 AU) and investigated further for one of the sources on smaller scales.Results.The radii of the fitted disk-like structures range from∼90−170 AU, and the derived masses depend on the method. Usingthe Gaussian disk model results in masses of 54−556×10−3M, and using the power-law disk model gives 9−140×10−3M. Whilethe disk radii agree with previous estimates the masses are different for some of the sources studied. Assuming a typical temperaturedistribution (r−0.5), the fractional amount of mass in the disk above 100 K varies from 7% to 30%.Conclusions.A thin disk model can approximate the emission and physical structure in the inner few 100 AU scales of the stud-ied deeply embedded low-mass protostars and paves the way for analysis of a larger sample with ALMA. Kinematic data areneeded to determine the presence of any Keplerian disk. Using previous observations of p-H182O, we estimate the relative gas phasewater abundances relative to total warm H2to be 6.2×10−5(IRAS 2A), 0.33×10−5(IRAS 4A-NW), 1.8×10−7(IRAS 4B),and<2×10−7(IRAS 4A-SE), roughly an order of magnitude higher than previously inferred when both warm and cold H2wereused as reference. A spherically symmetric single power-law envelope model fails to simultaneously reproduce both the small- andlarge-scale emission.
Gesehen am 23.09.2020